Status of humoral immune factors in peripheral blood of fronto-orbital trauma patients late after surgery with the use of biocomposite (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To identify the influence of biocomposite on immune system status in front bone trauma (FBT) patients at 9 months or later after surgery involving the use of the composite material.Material and Methods: Twenty FBT patients underwent an examination 9 months or later after surgery. They were divided into two groups, group A with a problematic clinical course and group B with an uneventful clinical course during follow-up. The control group was composed of 10 age-matched and practically healthy individuals. Serum levels of immunoglobulin (Ig)M, IgG, IgA and IgE, interleukins (IL)-1 and IL-10, transforming growth factor (TGF)-?, circulating immune complexes (CIC), and gamma interferon (IFN-?), and agglutination antibodies to antigens of allogeneic connective tissue were measured. Non-parametric Wilcoxon U test and Student t-test were used for statistical analysis.Results: Activation of pro- and anti-inflammatory interleukins and no changes in the levels of immunoglobulins and CIC were found in group A, but not group B or the controls. In addition, patients from group A exhibited decreased serum levels of TGF-? and IFN-?, which may be considered as pathogenetically significant factors involved in regeneration processes. No humoral autoimmune response to connective tissue antigens was found.Conclusion: Two disease course variants were found in the late phase after FBT. Increased serum levels of pro- and anti-inflammatory interleukins and decreased serum levels of TGF-? and, especially, IFN-?, were observed in patients with problematic regeneration. No humoral autoimmune response to connective tissue antigens was found in either group of patients with FBT. Stress mechanisms might be involved in decreased immunity levels in these patients.
Keywords: trauma; immunoglobulins; cytokines; growth factor; immune complexes; humoral autoimmune responses